The Role of Digital Marketing in Increasing Customer Loyalty in Start-Up Businesses at PT Elther Jaya Solusindo - Sri Rahayu, Feby; Insani, Siti (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This research aims to analyze the role of digital marketing in enhancing customer loyalty in the start-up business of PT Elther Jaya Solusindo. The study employed a descriptive qualitative method with data collected through interviews, observations, and documentation studies. The findings reveal that digital marketing strategies significantly influence customer loyalty through improved trust, engagement, and customer experience. The company utilizes social media platforms such as Instagram, TikTok, and WhatsApp Business to establish interactive and responsive two-way communication. Key factors affecting customer loyalty include response speed, digital content quality, and personalized approaches that foster emotional attachment. Overall, PT Elther Jaya Solusindo’s digital marketing strategy effectively builds long-term relationships and strengthens customer loyalty amid the digital transformation era.